Standardized Patient Case: Paul/Paula Byers, Schizophrenia - Matthew Goldenberg; Molly Hall; Graceanne Adamo; Lisa Rawn; Derrick Hamaoka; Judith Wilber (Association of American Medical Colleges, 2011)
Abstract This standardized patient case was designed as a formative educational experience to enhance medical trainees' skills in psychiatric interviewing and case formulation. This case provides an opportunity for trainees to interview Paul/Paula Byers, a patient with psychotic symptoms. The encounter allows students to gain familiarity with symptoms of schizophrenia including affective blunting, speech latency, paranoid thoughts, hallucinations, and aggressive ideation. The trainees have an opportunity to experience a challenging interview in that the patient speaks slowly, displays little to no social reciprocity, has bizarre beliefs, and has poor insight into his/her illness. Students have an opportunity to hone their skills in handling difficult situations, including having to be patient in awaiting answers and exploring delusional content. The case also allows for the evaluation and consideration of a patient's risk toward others and can be utilized for a postencounter discussion of professional duty to warn and protect.